Overview and Analysis of the Indian Gaming Industry - Patil, Suraj; Bachani, Yukta (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
The smartphone boom has given rise to mobile gaming in India, which is a relatively new market. The paper intends to provide an overview of the industry, with current trends and practices rampant across the sector. The reasons for its growth, possible opportunities in the next 5 years and the impact COVID-19 had will be investigated, along with parallels drawn to the video gaming industry. Data has been collected from both primary and secondary sources and analyzed for further clarity on the subject in the form of various diagrams and models. The aim is to gain a clearer understanding of the sector and evaluate whether it has the potential and impact it is believed to have. We also collected data by conducting survey by circulating google forms, in which we asked them various questions that would help us with our research. the survey shows that mobile gaming is indeed a popular form of entertainment and gaming. It had 48 respondents, out of which 77% did in fact play mobile games. The ages are between 17 to 28. The average age of our sample population is 23 years.